Living soil : a grower's guide - Fortier, Jean-Martin (Grower's guides from the market gardener, 2025)
"Living Soil: A Grower's Guide offers an illustrated, accessible resource on nurturing resilient crops and ecosystems through fertile, healthy soil. Jean-Martin Fortier shares his proven biointensive methods to help growers understand soil biology, improve fertility, and cultivate lasting abundance."--